Molecular and Phylogenomic Analysis of a Vancomycin Intermediate Resistance usa300lv Strain in Chile - Vecchiola-Herman, M; Vasquez-Martinez, y; Cespedes-Lacombe, A; Fonseca-Cortes, C; Garay-Munoz, T; Cortez-San Martin, M; Michelson-Quintana, S; Maldonado-Soto, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Antimicrobial resistance is a major global health problem, and, among Gram-positive bacteria, methicillin-resistant Staphylococcus aureus (MRSA) represents a serious threat. MRSA causes a wide range of infections, including bacteremia, which, due to the limited use of β-lactams, is difficult to treat. This study aimed to analyze 51 MRSA isolates collected in 2018 from samples of patients with bacteremia from two hospitals of the Metropolitan Health Service of Santiago, Chile, both in their resistance profile and in the identification of virulence factors. In addition, genomic characterization was carried out by the WGS of an isolate that was shown to be the one of greatest concern (N°. 42) due to its intermediate resistance to vancomycin, multiple virulence factors and being classified as ST8 PVL-positive. In our study, most of the isolates turned out to be multidrug-resistant, but there are still therapeutic options, such as tetracycline, rifampicin, chloramphenicol and vancomycin, which are currently used for MRSA infections; however, 18% were PVL positive, which suggests greater virulence of these isolates. It was determined that isolate N°42 is grouped within the USA300-LV strains (ST8, PVL+, COMER+); however, it has been suggested that, in Chile, a complete displacement of the PVL-negative ST5 clone has not occurred. © 2024 by the authors.